-12n+6=-10n-2

Simple and best practice solution for -12n+6=-10n-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -12n+6=-10n-2 equation:


Simplifying
-12n + 6 = -10n + -2

Reorder the terms:
6 + -12n = -10n + -2

Reorder the terms:
6 + -12n = -2 + -10n

Solving
6 + -12n = -2 + -10n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '10n' to each side of the equation.
6 + -12n + 10n = -2 + -10n + 10n

Combine like terms: -12n + 10n = -2n
6 + -2n = -2 + -10n + 10n

Combine like terms: -10n + 10n = 0
6 + -2n = -2 + 0
6 + -2n = -2

Add '-6' to each side of the equation.
6 + -6 + -2n = -2 + -6

Combine like terms: 6 + -6 = 0
0 + -2n = -2 + -6
-2n = -2 + -6

Combine like terms: -2 + -6 = -8
-2n = -8

Divide each side by '-2'.
n = 4

Simplifying
n = 4

See similar equations:

| 2(4a-7)+a=76 | | -37-(-43)=x/6 | | 2(4c-1)-6=3c+7 | | -7(t+1)=14 | | -7(t+1)=4 | | 1/2(18x+2)=3(3x-2)-3(x-7) | | 1/2(p+6)=7/2(3-p) | | 3x^2+(k-1)x-2=0 | | 27-19=4(x-6) | | -7x+1=9 | | 30+5y-12=17y-9-3y | | x+23+4x=-22-4x-27 | | -x(x-2)(x+2)(x+2)=0 | | b^12*b^10= | | -0.4x^2+2.2x+4.7=0 | | w^6*w^8= | | 5q^2-2bq-3=0 | | -4x+1=33 | | 2m/5+4=-10/9-3 | | P(2)-10P+22=0 | | 3(z-4)+6= | | -11/7=z-2/3 | | 2log(x-3)-log(x+1)=2 | | k*k^12= | | 4x^2+7x=6 | | a^4-6a^2+5=0 | | 6+2(1+2x)=29-3x | | 2x-7(3-2x)=11 | | 2((1.5+2)+(1.5+3))=16 | | 154=4x^2+26x+40 | | -4+4x=-8 | | 2((x+2)+(x+3))=16 |

Equations solver categories